The Implementation Of Interactive Learning Strategy To Formulating Learning Objectives In Package C Program - Yanti Karmila Nengsih; Ciptro Handrianto; Piki Setri Pernantah; Ary Kiswanto Kenedi; Amayra Tannoubi (Universitas Negeri Padang, 2022)
The implementation of interactive learning strategy in teaching-learning activities may encourage multiple interaction between tutors and learners to achieve their learning objectives. This study aims to identify the effectiveness of interactive learning strategy by tutors to formulate learning objectives among learners in Package C program. The methodology used in this study is quantitative with descriptive approach in analysing the data. There were 30 Package C learners in Binuang Sakti Group in Padang involved with this study. They filled in the questionnaire related to their perception on interactive learning strategy applied by tutors during their study in Package C program. The results of the study show that majority of learners agree that the tutors helped them to formulate learning objectives by implementing interactive learning in their classes. The conclusion of study is that the implementation of interactive learning in Binuang Sakti Group of Package C in Padang is effective to help learners to determine their learning objectives to participate in Package C program.